The prognostic capability of inflammatory proteins in predicting peripheral artery disease related adverse events - Li, Ben; Djahanpour, Niousha; Zamzam, Abdelrahman; Syed, Muzammil H.; Jain, Shubha; Arfan, Sara; Abdin, Rawand; Qadura, Mohammad (Frontiers in Cardiovascular Medicine, 2022)
Background Levels of inflammatory proteins and their prognostic potential have been inadequately studied in patients with peripheral artery disease (PAD). In this study, we quantified and assessed the ability of inflammatory proteins in predicting PAD-related adverse events. Methods In this prospective case-control study, blood samples were collected from patients without PAD (n = 202) and patients with PAD (n = 275). The PAD cohort was stratified by disease severity based on ankle brachial index (ABI): mild (n = 49), moderate (n = 164), and severe (n = 62). Patients were followed for 2 years. Plasma concentrations of 5 inflammatory proteins were measured: Alpha-2-Macroglobulin (A2M), Fetuin A, Alpha-1-Acid Glycoprotein (AGP), Serum Amyloid P component (SAP), and Adipsin. The primary outcome of our study was major adverse limb event (MALE), defined as the need for vascular intervention (open or endovascular revascularization) or major amputation. The secondary outcome was worsening PAD status, defined as a drop in ABI greater than or equal to 0.15 over the study period. Multivariable logistic regression was performed to assess the prognostic value of inflammatory proteins in predicting MALE, adjusting for confounding variables. Results Compared to patients without PAD, three inflammatory proteins were differentially expressed in patients with PAD (AGP, Fetuin A, and SAP). The primary outcome (MALE) and secondary outcome (worsening PAD) status were noted in 69 (25%) and 60 (22%) patients, respectively. PAD-related adverse events occurred more frequently in severe PAD patients. Based on our data, the inflammatory protein AGP was the most reliable predictor of primary and secondary outcomes. On multivariable analysis, there was a significant association between AGP and MALE in all PAD disease states [mild: adjusted HR 1.13 (95% CI 1.05–1.47), moderate: adjusted HR 1.23 (95% CI 1.16–1.73), severe: adjusted HR 1.37 (95% CI 1.25–1.85)]. High levels of AGP were associated with lower 2-year MALE-free survival in all PAD disease states [mild (64% vs. 100%, p = 0.02), moderate (64% vs. 85%, p = 0.02), severe (55% vs. 88%, p = 0.02), all PAD (62% vs. 88%, p = 0.01)]. Conclusion Levels of inflammatory protein AGP may help in risk stratifying PAD patients at high risk of MALE and worsening PAD status and subsequently facilitate further vascular evaluation and initiation of aggressive medical/surgical management.